Studi Literatur: Politik Uang Dalam Pemilihan Kepala Daerah di Indonesia - puansah, irman (Universitas Muhammadiyah Tapanuli Selatan, 2024)
Money politics in regional elections (Pilkada) in Indonesia reflects the complexity of issues involving various social, economic, and legal aspects. Addressing this problem requires a comprehensive approach, including enhancing public political education, reforming law enforcement, and efforts to reduce political costs. By doing so, it is hoped that money politics practices can be minimized, and regional elections can be conducted in a cleaner and more democratic manner, resulting in leaders truly committed to serving the public interest. This study aims to gain a deeper understanding of the patterns, causes, and impacts of money politics practices. The research method used is a literature study, collecting information by understanding and studying theories from various related literature. The results of the study show that money politics in Indonesia harms elections, violates democratic principles, and is difficult to prosecute legally. Electoral system reforms are needed to tackle money politics and strengthen the integrity of democracy and public trust. Money politics is influenced by economic factors, low political education, cultural norms, political power, and weaknesses in oversight. The practice of money politics in Indonesia undermines democracy by fostering corruption, injustice, and reducing public trust. The high cost of elections reinforces political corruption, reduces fair representation, and increases the risk of clientelism, which undermines moral values and the quality of democracy.